Speech Acts Variation in Social Media Instagram @punapibali - Putu Nindhya Nirmala; I Nyoman Kardana; Agus Darma Yoga Pratama (RETORIKA: Jurnal Ilmu Bahasa, 2021)
This research aims to examine the speech act functions found on Instagram @punapibali and describe the types of speech acts used by the informant and news writer. Thus, this study was conducted using the qualitative descriptive method and by using the pragmatics fundamentals proposed by Wijana (1996) and the speech act function theory of Searle (1979) as the basis for examining the speech act functions used by the informant and news writer according to its type. The data were collected through the observation method accompanied by an act of scrutinizing speeches and sentences of the informant and news writer @punapibali. The oral data were collected from the conversations use to know the intonation and tone of the speech delivered. The data analysis results are presented descriptively. The results of data analysis showed there are 40 types of speech acts used in the caption of Instagram @punapibali. The expressive function is manifested in the act of asking for an apology, thanking someone, and congratulating someone. The directive function includes the act of asking, suggesting, advising, and urging. The commissive function includes expressing abilities and promising. The assertive function includes notifying, affirming, and stating. The declarative function is manifested in the act of declaration.